Persepsi, Pengetahuan Akuntansi dan Pengalaman Usaha Terhadap Penggunaan Informasi Pada UMKM - Agustinus Putra Pamungkas; Ika Kristianti (AFRE (Accounting and Financial Review), 2019)
The purpose of this research was to determine the effect of perceptions and accounting knowledge on the use of accounting information. This research  adds a moderating variable that is to strengthen the relationship between perception, accounting knowledge on the use of accounting information. The data obtained are primary data sourced from questionnaires and direct interviews with MSMEs and the analysis technique used is multiple regression analysis. The results of this research indicate that the moderating variable does not strengthen or weaken the perception and accounting knowledge variables of the use of accounting information. DOI: https://doi.org/10.26905/afr.v2i2.3729